A STUDY OF POSTERIOR CHAMBER INTRAOCULAR LENS IMPLANTATION - Awan, Abdul Aziz (Journal of Ayub Medical College Abbottabad, 1995)
ABSTRACT: 200 cases of extracapsular extraction with Posterior Chamber intra-ocular lens implantation were studied between February, 1988 to April, 1994 at DHQ Teaching Hospital, Abbottabad and were followed up, with a view to measure post-op refractive errors and complications. The procedure was performed either under GA or under Peribulbar anaesthesia using operating microscope, IOL were inserted with the help of air bubble or methyl cellulose. Michol or acetylcholine were used in selected cases. (21 % of the patients had visual acuity of 6/6 without any glasses. 72.6% had visual acuity of 6/9 or more with spherical correction of +2D/-2D. 7.8% of the patients developed after cataract which needed yag Laser or capsulotomy). The procedure is treatment of choice for unilateral and senile cataract without any additional complication then seen in routine E.C.C.E. No extra risk of post-operative complications is experienced